Analysis of Patient Service Manager Competencies and Strategies in Handling Patient Complaints at Dr. Iskak Tulungagung Hospital - Wicaksono, Gunawan; Sentot Imam Suprapto; Yenny Puspitasari (STRADA : Jurnal Ilmiah Kesehatan, 2025)
Patient complaints are an important indicator of dissatisfaction with healthcare services and require systematic handling to support continuous quality improvement. This qualitative study explored the competencies and strategies of Patient Service Managers (MPPs) in handling patient complaints at Dr. Iskak Tulungagung Hospital. Using a phenomenological approach, 14 room heads were interviewed as primary informants, supported by triangulation with two division heads. Data were collected through semi-structured interviews, observation, and documentation review. The findings show that MPPs demonstrate adequate competencies including communication skills, collaboration, advocacy, and resource management although some have not completed ACM certification.